2018
DOI: 10.1021/acssuschemeng.7b03871
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Interconnected 3D Pore Network Algal Biochar Constituting Iron Nanoparticles Derived from a Harmful Marine Biomass as High-Performance Asymmetric Supercapacitor Electrodes

Abstract: Via the activation treatment on Cladophora glomerata (CG) with FeCl 3 and KOH, magnetic biochar (MBC) with olive-shaped pores and functional biochar (FBC) with a novel interconnected 3D pore network structure have been successfully prepared by a facile slow pyrolysis process to be applied as electrodes in supercapacitors. To obtain Fe composite biochar (FCBC), FBC was functionalized with HNO 3 and H 2 SO 4 for extending formation of iron oxide through the hydrothermal method. These electrodes demonstrate remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(53 citation statements)
references
References 80 publications
2
51
0
Order By: Relevance
“…Ac omparison of the Ragoneplots obtained for ASCs constructedf rom BDC materials reported herein. CNB/MnO 2 @CNB (BDC = tofu), [128] AMC/ZnCO (BDC = almond shells), [122] EDAC/MnS (BDC = eggplant), [145] NPC/PC@MnO 2 (BDC = loofah sponge), [130] NKGLC/Ni(OH) 2 -MnO 2 -rGO (BDC = ginkgo leaf), [158] PC/NiCo 2 S 4 @PC (BDC = popcorn pieces), [156] APC/NiCo 2 O 4 (BDC = walnut shells), [151] HC/MnO 2 @HC (BDC = hemps tems), [126] PFN/PFNC (BDC = pomelo fruit), [150] BioHPC/NiCo 2 O 4 -NS (BDC = corncob), [152] N-CBC/CBC-N@LDH (BDC = bacterial cellulose pellicles), [133] p-BC-N/MnO 2 @p-BC (BDC = bacterialcellulose pellicles), [87] HSC/Ni-Co-Al LDH (BDC = bacterial cellulose pellicles), [134] CCNS/ MnO 2 @CCNS (BDC = willowc atkin) [57] PCMT/b-Ni(OH) 2 @ACMT (BDC = willow catkin), [89] FBC/FCBC (BDC = CG), [154] Fe 2 O 3 @BPC/CNT@CoNiLDH( BDC = wheat straw), [157] GPCN-SS/ MnO 2 @GPCN-SS( BDC = SS), [135] and MnSi-C/Ni(OH) 2 (BDC = bambool eaves). [147] Figure 15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ac omparison of the Ragoneplots obtained for ASCs constructedf rom BDC materials reported herein. CNB/MnO 2 @CNB (BDC = tofu), [128] AMC/ZnCO (BDC = almond shells), [122] EDAC/MnS (BDC = eggplant), [145] NPC/PC@MnO 2 (BDC = loofah sponge), [130] NKGLC/Ni(OH) 2 -MnO 2 -rGO (BDC = ginkgo leaf), [158] PC/NiCo 2 S 4 @PC (BDC = popcorn pieces), [156] APC/NiCo 2 O 4 (BDC = walnut shells), [151] HC/MnO 2 @HC (BDC = hemps tems), [126] PFN/PFNC (BDC = pomelo fruit), [150] BioHPC/NiCo 2 O 4 -NS (BDC = corncob), [152] N-CBC/CBC-N@LDH (BDC = bacterial cellulose pellicles), [133] p-BC-N/MnO 2 @p-BC (BDC = bacterialcellulose pellicles), [87] HSC/Ni-Co-Al LDH (BDC = bacterial cellulose pellicles), [134] CCNS/ MnO 2 @CCNS (BDC = willowc atkin) [57] PCMT/b-Ni(OH) 2 @ACMT (BDC = willow catkin), [89] FBC/FCBC (BDC = CG), [154] Fe 2 O 3 @BPC/CNT@CoNiLDH( BDC = wheat straw), [157] GPCN-SS/ MnO 2 @GPCN-SS( BDC = SS), [135] and MnSi-C/Ni(OH) 2 (BDC = bambool eaves). [147] Figure 15.…”
Section: Discussionmentioning
confidence: 99%
“…[154] CG wass tirred in a solution of FeCl 3 and the dried material was then pyrolyzed at 700 8Cf or 4hunder an argon atmosphere to give magnetic biochar (MBC). [154] CG wass tirred in a solution of FeCl 3 and the dried material was then pyrolyzed at 700 8Cf or 4hunder an argon atmosphere to give magnetic biochar (MBC).…”
Section: Cladophora Glomeratamentioning
confidence: 99%
See 1 more Smart Citation
“…The SSA of CF20 is ∼190 m 2 g −1 which is lesser than CF0 and CF10 (Figure S3b). The decrease in CF20 SSA might be due to the higher loading of iron oxide which occupied the void and surface space in the layered material …”
Section: Resultsmentioning
confidence: 99%
“…The drastically decrease in CF20 SSA might be due to higher loading of iron oxide which occupied the void space in the layered material. [33][34] CF0 and CF20 as compared to CF10 as Csp is directly related to the area under the CV curve. On the basis of above discussion, it could be concluded that CF10 has the best capacitive performance.…”
Section: Resultsmentioning
confidence: 99%